Effect of Leader-Member Exchange and Organization Climate towards Public Sector Employee Performance Mediated by Innovative Work Behavior - Brama Ardianto; Suharnomo Suharnomo (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to analyze how much influence the leader-member exchange, organizational climate and innovative work behavior improve employee performance of Directorate General X of Ministry Y. This research uses quantitative methods. This study used structural equation modeling (SEM) analysis techniques. Sampling is used purposive sampling method. This study took a sample of civil servants who had worked as research subjects for at least 2 years. Employees with structural officer positions or functional officers who serve as coordinators and sub-coordinators are not included because this study focuses on employees who do not occupy managerial positions. From the discussion above, the leader-member exchange positively affects employee performance. The organizational climate positively affects employee performance. Leader-member exchanges positively affect employees' innovative work behaviors. The organizational climate positively affects the innovative work behavior of employees. Innovation work behavior has a positive effect on employee performance. Innovation work behavior partially mediates the relationship of the influence of member leadership exchanges on employee performance. Innovation work behavior partially mediates the relationship between the influence of the organizational climate on employee performance.